Efeitos da Angiotensina-(1-7) e Alamandina na polarização in vitro de macrófagos murínicos para os fenótipos M1 E M2A - Melissa de Carvalho Santuchi (2017)
Background: Macrophages activated to M1 and M2a phenotypes are considered important effectors in several pathophysiological conditions such as inflammation and cardiovascular diseases. Angiotensin-(1-7) [Ang-(1-7)] decreases the inflammatory response of some genes in M1, but its effect on other cytokines and on the M2a phenotype is not known. There are no reports of the effect of alamandine, a newly characterized component of the reninangiotensin system, on macrophage polarization. Aim: To evaluate the effect of Ang-(1-7) and alamandine on the phenotypic profile of macrophages M1 and M2a from bone marrowderived macrophages of FVB/N mice in vitro. Methods: Bone marrow cells obtained from femurs and tibias of adult WT FVB/N mice were cultured for 8 days. In vitro polarization was performed in M1 (IFN-γ and LPS) and M2 (IL-4) during 4 hours, followed by vehicle, Ang-(17) or alamandine treatments, with both peptides at 10-7M in each group. M1 and M2a were characterized by F-actin labeling and the expression of Arg-2, CCL2, IL-1β, IL-10, iNOS and TNFα (M1); And Arg-1, CD206, FIZZ-1, IL-10 and YM-1 (M2a) transcripts by qPCR. The contents of TNFα (ELISA) and NO2- (Griess method) were analyzed; and the production of EROs by DHE. The expression and localization of Mas and MrgD receptors in both phenotypes were also evaluated by qPCR and immunofluorescence. The effects of the peptides were assessed by qPCR and the role of the Mas and MrgD receptors in these was analyzed by the pharmacological antagonism using A779 and D-Pro. Results: No morphological differences were observed between M1 and M2a phenotypes. Treatments with Ang-(1-7) and alamandine decreased gene expression for M1 (TNFα, IL-1β and CCL2). In M2a, the expression of FIZZ-1 was not altered, but increased expression of the YM-1 transcript was observed with the treatment with the two peptides. Alamandine further reduced the expression of the CD206 transcript. Pharmacological antagonism of Mas and MrgD by A779 and D-Pro revealed that the effects observed on M1 are dependent on these receptors, respectively, except for IL-1β. In M2a, the observed effect does not seem to depend on these receptors. Conclusion: Using markers previously described in the literature, M1 and M2a have been characterized and it has been shown that both Ang-(1-7) and alamandine distinctly affect the polarization of these cells, decreasing the expression of a set of proinflammatory genes and acting in a smaller spectrum in the anti-inflammatory genes. This is the first report of the presence of the MrgD receptor in murine macrophages and the anti-inflammatory effect of the activation of the alamandine/MrgD pathway. Financial support: CAPES, CNPq, FAPEMIG and INCT Nanobiofar.